2013
DOI: 10.1074/jbc.m113.461269
|View full text |Cite
|
Sign up to set email alerts
|

The Amyloid Precursor Protein Represses Expression of Acetylcholinesterase in Neuronal Cell Lines

Abstract: Background: Acetylcholinesterase (AChE) and amyloid precursor protein (APP) are implicated in Alzheimer's disease, but their specific biological roles remain unclear. Results: Overexpression or knockdown of neuronal APP modulates AChE mRNA, protein levels, and enzyme activity. Conclusion: APP can act as a transcriptional regulator through a novel mechanism independently of ␥-secretase. Significance: Understanding the physiological functions of APP will lead to a greater understanding of Alzheimer's disease eti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 81 publications
(96 reference statements)
0
20
0
Order By: Relevance
“…An increasing list of AICD candidate genes has emerged from various models (reviewed in Pardossi-Piquard and Checler, 2012). On the other hand, APP was also reported to regulate gene transcription independently of AICD release (Hicks et al, 2013;Pierrot et al, 2013). It is thus so far quite impossible to clearly define (i) the precise identity of APP target genes in neurons (ii) the related molecular pathways underlying APP-dependent gene transcription (iii) how APP target genes relate to APP neuronal function.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing list of AICD candidate genes has emerged from various models (reviewed in Pardossi-Piquard and Checler, 2012). On the other hand, APP was also reported to regulate gene transcription independently of AICD release (Hicks et al, 2013;Pierrot et al, 2013). It is thus so far quite impossible to clearly define (i) the precise identity of APP target genes in neurons (ii) the related molecular pathways underlying APP-dependent gene transcription (iii) how APP target genes relate to APP neuronal function.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, APP-dependent Npas4 expression at DIV7 does not rely on AICD release, although DIV7 corresponds to the differentiation stage where AICD is readily produced by neurons (Kimberly et al, 2005). Previous studies indicated that regulation of some APP target genes does not require the generation of AICD (Hicks et al, 2013). Quite strikingly, DAPT treatments, used to block AICD production in our setup, increased Npas4 expression in APP+/+ neurons.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing list of AICD candidate genes has emerged from various models (reviewed in Pardossi-Piquard and Checler, 2012). Some of these candidate genes failed to be confirmed by transcription analysis in APP-deficient cell lines (Hebert et al, 2006; Waldron et al, 2008), and APP was also reported to regulate gene transcription independently of AICD release (Hicks et al, 2013; Pierrot et al, 2013). It is so far impossible to clearly define (i) the precise identity of APP target genes in neurons (ii) how these APP target genes relate to APP neuronal function (iii) the mechanism involved in APP-dependent in gene transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicate that APP‐dependent GDNF transcription is not relying on AICD by the γ‐secretase and, moreover, that APP751 isoforms lacking the C‐terminal region restore GDNF expression to a same extent than native APP751. GDNF might thus belong to another set of APP target genes, like the acetylcholinesterase gene, which is transcriptionally regulated by APP in an AICD‐independent manner (40). One possible hypothesis is that APP recruits through its ectodomain or transmembrane region partner protein directly involved in signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…region restore GDNF expression to a same extent than native APP751. GDNF might thus belong to another set of APP target genes, like the acetylcholinesterase gene, whichistranscriptionallyregulatedbyAPPinanAICDindependent manner (40). One possible hypothesis is t h a tA P Pr e c r u i t st h r o u g hi t se c t o d o m a i no rt r a n smembrane region partner protein directly involved in signal transduction.…”
Section: Discussionmentioning
confidence: 99%